Analisis Unjuk Kerja Four-Stroke Diesel Engine Dengan Bahan Bakar Multi-Feedstock Biodiesel (Minyak Kelapa Sawit, Minyak Kemiri, Minyak Biji Jarak) - Moch Alfian; Edi Haryono; Aminatus Sa'diyah (Proceedings Conference on Marine Engineering and its Application, 2023)
This study aims to analyze the performance of four-stroke diesel engines using multifeedstock biodiesel fuel (palm oil, candlenut oil, and castor seed oil). The three raw materials will be combined and will be mixed with pertamina dex, so that it becomes B20, B35, and B100. Experiments were carried out with engine speed variations of 900, 950, 1000, 1050 rpm and loading variations of 1000 watts, 2000, watts, and 3000 watts. The results showed that the use of multifeed-stock biodiesel B20, B35, and B100 affected the performance of the engine produced. Power and torque values tend to increase when using B20, B35, and B100 fuel. However, the gsfc value produced is not determined by the greater the percentage of biodiesel. B100 fuel is the highest fuel in producing power and shock, while B35 is the lowest gsfc value fuel.